Consumer Attitudes towards Furniture Buying at Limbang, Sarawak - Fatin, Arina Matusin (2016)
Since Malaysian furniture industry has undergo dynamic transformation, it makes Malaysia’s furniture export world ranking was 8th in 2011 for all types of furniture. Besides, the furniture industry can leverage on the rising demand for furniture in the growing domestic property sector. Other than catering for homes, Malaysian furniture industry also cater for hotels, stadiums, conference centres, schools, hospitals etc. This study suggests a research model that assists to determine consumer attitude towards furniture buying. The research study further on the relationship between furniture buying behaviour with the factors: quality, price, aesthetics, comfort, durability and availability. It is concluded that aesthetics and availability is the significant factors that influence furniture buying behaviour at Limbang, Sarawak. Furniture retailers in Limbang, Sarawak are benefitted from the research since they are able to determine the factors that influence furniture buying behaviour of their consumers. With improved aesthetics value of the furniture such as the design, color and material as well as availability where the retailers could meet their consumers demand, the sales could be increased and more understanding of consumer behaviour. This study also gives suggestions and recommendations for future research in related areas in Malaysia as well as the limitation of study is elaborated.